2014
DOI: 10.1638/2013-0274r1.1
|View full text |Cite
|
Sign up to set email alerts
|

HEMATURIA AND URINARY BLADDER LESIONS COMPATIBLE WITH BRACKEN FERN (PTERIDIUM AQUILINUM) INTOXICATION IN CAPTIVE FALLOW DEER (DAMA DAMA)

Abstract: Hemangiosarcoma, hemangioma, transitional cell carcinoma, and chronic cystitis were diagnosed in the urinary bladder of six captive fallow deer (Dama dama). Hematuria and thin body condition were observed in the advanced cases. These findings were compatible with chronic enzootic hematuria and were suspected to have been induced by chronic ingestion of bracken fern (Pteridium aquilinum) present on the premises. These lesions were similar to those described in bovine enzootic hematuria in cattle. Hemangiosarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…41 In this context, it is worthwhile remembering that urinary bladder tumors caused by ptaquiloside, 1, intoxication have recently been described, for the first time, in captive fallow deer. 42 Furthermore, a novel syndrome characterized by intestinal adenocarcinomas in adult farmed Sika deer that have grazed on bracken-infested pastures has just been described. Therefore, it has been suggested that ptaquiloside, 1, plays a crucial role in deer intestinal tumorigenesis too.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…41 In this context, it is worthwhile remembering that urinary bladder tumors caused by ptaquiloside, 1, intoxication have recently been described, for the first time, in captive fallow deer. 42 Furthermore, a novel syndrome characterized by intestinal adenocarcinomas in adult farmed Sika deer that have grazed on bracken-infested pastures has just been described. Therefore, it has been suggested that ptaquiloside, 1, plays a crucial role in deer intestinal tumorigenesis too.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Great eagle fern (Pteridium aquilinum), also called bracken fern, is an invasive plant that grows globally in very diverse environments and is difficult control in pastures [7]. Intoxication following ingestion is well documented in ruminants, including cattle, sheep and wild cervids [8,9]. In cattle, bracken fern ingestion causes enzootic haematuria, characterized by lower urinary tract haemorrhages and neoplasms of epithelial and mesenchymal origin [9].…”
Section: Introductionmentioning
confidence: 99%
“…The great eagle fern (Pteridium aquilinum) is an invasive plant that grows globally in very diverse environments, leading to it being di cult control in pastures [7]. Intoxication following ingestion is well documented in ruminants, including cattle, sheep and wild cervids [8,9]. In cattle, bracken fern ingestion causes enzootic haematuria, characterized by lower urinary tracts haemorrhages and neoplasms of epithelial and mesenchymal origins [9].…”
Section: Introductionmentioning
confidence: 99%
“…Intoxication following ingestion is well documented in ruminants, including cattle, sheep and wild cervids [8,9]. In cattle, bracken fern ingestion causes enzootic haematuria, characterized by lower urinary tracts haemorrhages and neoplasms of epithelial and mesenchymal origins [9]. Additionally, acute haemorrhagic syndrome, secondary to bone marrow aplasia and retinal atrophy have been documented in sheep [8], as has polioencephalomalacia [10].…”
Section: Introductionmentioning
confidence: 99%